A ironia no texto sincrético: estudo de textos sincréticos irônicos, na seção Veja essa , da revista Veja - Peres, Silvia Regina (2008)
The present research intends to analyze the ironic syncretic text of the section named Veja essa weekly published in Veja magazine. Among lots of sections which compose the magazine, we detached Veja essa section that consists in a compilation of phrases pronounced by exponentials personalities generally politicians and some persons of the social, cultural and sport fields who deserved some highlight during the week that corresponding to magazine s edition. These selected phrases are displayed with captions to inform its origin and context. Sometimes a picture illustrate the phrase and not often the picture used has no relation to the situation when the phrase has spoken. Therefore, when both components one of them a verbal while other a nonverbal are merged in magazine s page, a new kind of text come to sight: the syncretic text, created by magazine. This new text suggest an ironic reading. The irony referred could only be identified and interpreted if the reader had some knowledge about subject in question and also about political and ideological magazine s position. When recognized by the reader, irony can assume several functions as the humoristic for instance. Usually these analyzed texts brings out a sarcastic humor since we could note an aggressiveness as much as a disqualification of the central s text personage.